(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article delves into the realm of filological exploration, unraveling the intricate threads that weave the narratives of Abdulrazzaq Gurnah’s “Paradise” and Shuhrat’s “Searching for Paradise”. Employing a meticulous examination of artistic likeness, the experiences of characters, and the underlying purpose embedded within the works, this study aims to shed light on the profound literary significance encapsulated in these novels.